“Jamaican Sound Keroncong”: A Communication Study on the Spread of Keroncong in the Young Generation in Bandung - Supiarza, Hery; Sobarna, Cece (Bina Nusantara University, 2019)
This research discussed Jamaican Sound Keroncong (JSK) as a communication media in the global era. The problem of research was that keroncong music tended to be unknown by most young people in Bandung, and it was lost almost a century among them. This research aimed to examine the communication between the structure, agents (SirIyai), and sub-agents (Crispy Crue/the fans), and the appreciation of the keroncong community in Bandung for their performances. Spredlay ethnographic methods were applied. SirIyai was trusted informants and participatory observations, and in-depth interviews were carried out within one year. The research finds that; (1) SirIyai creates a communication media product under the name of JSK as the binding structure between SirIyai as the agent and CCI as the sub-agent; (2) the development of the internet creates dynamics and generates communication space; (3) communication of musical instruments is the basic idea of JSK product creation as communication media; and (4) there is a fundamental change of the old keroncong communication system to that of the youth keroncong in the global era. SirIyai is considered as the role model of the recent keroncong communication and becomes the parameter of creativity of musical mixture of global music era in Bandung.